2004
DOI: 10.1016/j.contraception.2004.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive failure in the United States

Abstract: This review provides an update of previous estimates of first-year probabilities of contraceptive failure for all methods of contraception available in the United States. Estimates are provided of probabilities of failure during typical use (which includes both incorrect and inconsistent use) and during perfect use (correct and consistent use). The difference between these two probabilities reveals the consequences of imperfect use; it depends both on how unforgiving of imperfect use a method is and on how har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
539
3
25

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 581 publications
(580 citation statements)
references
References 61 publications
13
539
3
25
Order By: Relevance
“…The differences in pregnancy rates between the monitor and mucus group are similar to the differences that were found in a previous cohort comparison study of the monitor plus mucus versus mucus alone as two FABM [15]. The low unintended pregnancy rate (both perfect and total) are comparable to the pregnancy rates that were determined in a large European study that used mucus plus basal body temperature as a double check for the beginning and end of the fertile phase of the menstrual cycle [24] and with a pilot cohort study of the online FABM system conducted by the authors of this study, i.e., 9 unintended pregnancies per 100 among ovulating, non-breastfeeding participants [14].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The differences in pregnancy rates between the monitor and mucus group are similar to the differences that were found in a previous cohort comparison study of the monitor plus mucus versus mucus alone as two FABM [15]. The low unintended pregnancy rate (both perfect and total) are comparable to the pregnancy rates that were determined in a large European study that used mucus plus basal body temperature as a double check for the beginning and end of the fertile phase of the menstrual cycle [24] and with a pilot cohort study of the online FABM system conducted by the authors of this study, i.e., 9 unintended pregnancies per 100 among ovulating, non-breastfeeding participants [14].…”
Section: Discussionsupporting
confidence: 81%
“…The total unintended pregnancy rates for the monitor group in the current study are better than those reported by Trussell for FABM [24,25], i.e., 7 for the monitor group compared to 25 per 100 women by Trussell. The mucus group with 18 unintended pregnancies per 100 is comparable but slightly better than what Trussell reports for the mucus-only OM.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…A key factor in distinguishing between traditional and modern contraceptive methods is their effectiveness in preventing conception (Frejka 2008), although not all modern methods are similarly effective (Trussell 2011). Female reversible methods are very effective, as are male and female sterilization, whereas male reversible methods have higher failure rates.…”
Section: Introductionmentioning
confidence: 99%
“…In line, the theoretical framework first focuses on gender equality and contraception at the individual and couple level, and then looks at the regional variation in this relationship. Data from the Generations and Gender Survey (2004-2011GGP Data Archive 2016) and the Demographic Health Survey (2005)(2006)(2007)(2008)(2009)) are used to examine the hypotheses. absolute or relative power leads men and women to use contraceptives themselves or to transfer this task to their partner.…”
Section: Introductionmentioning
confidence: 99%